The Influence of Micro Influencers and Celebrity Endorsers on Tourists Interest and Intention to Visit Solo Safari - Nafiah Az Zahra; Muzakar Isa (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the influence of micro-influencers and celebrity endorsers on tourists’ interest and intention to visit Solo Safari. Grounded in the theories of persuasion, source credibility, and social influence, the study employs purposive sampling to target respondents with prior exposure to influencer content related to tourism, ensuring the relevance and contextual fit of the data. A total of 200 qualified respondents were selected, and data collection took place in Surakarta, Indonesia, from September to December 2024. Out of 234 collected responses, only valid entries were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The findings demonstrate that both micro-influencers and celebrity endorsers significantly influence tourist interest and visit intention. Micro-influencers drive engagement through authenticity, relatability, and audience trust, while celebrity endorsers contribute through their popularity and perceived expertise. Tourist interest acts as a mediating factor, bridging influencer impact and behavioral intention. While the sample size is adequate, expanding it in future research would improve representativeness, especially considering demographic factors such as age, gender, and nationality. Though context-specific, these findings may provide useful insights for similar urban tourism destinations, pending further cross-regional validation. Limitations related to PLS-SEM, such as model fit concerns, potential measurement bias, and multicollinearity, were addressed through validity and reliability tests to ensure robustness of the model.